Long Run Risks, Credit Markets, and Financial Structure - Bhamra, Harjoat S; Kuehn, Lars-Alexander; Strebulaev, Ilya A (American Economic Review, 2010)
Long Run Risks, Credit Markets, and Financial Structure by Harjoat S. Bhamra, Lars-Alexander Kuehn and Ilya A. Strebulaev. Published in volume 100, issue 2, pages 547-51 of American Economic Review, May 2010